Measuring executive function skills in young children in Kenya: Associations with school readiness. Issue 5 (15th March 2019) - Willoughby, Michael T.; Piper, Benjamin; Oyanga, Arbogast; Merseth King, Katherine
Abstract: Most of what is known about the association between children's executive function (EF) and school readiness skills is derived from research conducted in Western countries. We tested whether these associations were evident in a middle‐income country context. Participants were 1, 480 children, aged 4–7 years old, who participated in an endline assessment of the Tayari program, an early childhood education (ECE) model that is being delivered by the Kenyan education system. High rates of task completion, low rates of floor effects, and high rates of assessor quality ratings supported the feasibility of large‐scale direct assessments of EF with young children. Assessor ratings of children's attention‐related behaviors during testing were positively associated with their performance on EF tasks ( r s = 0.12–0.27). An EF composite score was not related to demographic factors or to children's exposure to the Tayari program. However, the EF composite score was uniquely associated with performance‐based measures of early literacy ( β  = 0.18, 95% confidence interval [CI] = 0.05, 0.31), early numeracy ( β  = 0.16, 95% CI = 0.07, 26), and social‐emotional competencies ( β  = 0.12, 95% CI = 0.03, 0.20), even after adjustment for multiple covariates. These results are discussed with respect to the ways in which EF skills inform ongoing efforts to invest in ECE in low‐ and middle‐income countries. Abstract : Most of what is known about the association between young children's executive function (EF) and school readiness skills is derived from research conducted in high‐income countries. This study was the first large‐scale, computerized assessment of EF skills among preprimary‐aged children in a middle‐income country, Kenya. A composite measure of EF skills was uniquely related to three domains of school readiness: pre‐literacy, pre‐numeracy, and social‐emotional competencies, and the magnitude of these associations was comparable to what has been observed in Western samples. This study provides initial data to support efforts to improve EF skills as a strategy for enhancing early school success.